Constitutive behaviors of steel fiber reinforced concrete under uniaxial compression and tension. (10th February 2020) - Shi, Xijun; Park, Philip; Rew, Younho; Huang, Kaijian; Sim, Chungwook
Highlights: Capturing full-range constitutive behaviors of the SFRC mixtures under both compression and tension. Evaluating the effect of steel fibers on various constitutive parameters using statistical analyses. Idealizing the compressive and tensile stress-strain curves of the tested SFRC mixtures. Abstract: Full-range constitutive curves for steel fiber reinforced concrete (SFRC) mixtures under both uniaxial compression and uniaxial tension are generally unavailable in the literature. Two types of the SFRC (straight and hooked fibers) with various fiber volume contents under uniaxial compression and tension were investigated. The results showed that the fibers remarkably enhanced the concrete post-cracking behaviors in terms of achieving higher ductility, residual strength, and toughness under compression and tension. The data collected in this study and that from the existing publications were used to evaluate the effect of steel fibers on various constitutive parameters of SFRC via statistical hypothesis tests. It was statistically evident that the tensile strength, and the strain at the peak load under either compression or tension are positively correlated with the fiber reinforcing index (RI), while there is no sufficient evidence indicating that the modulus of elasticity and compressive strength can be correlated with the RI. Finally, the constitutive behaviors of the studied mixtures were idealized, and the strain and stress coefficients from the idealized curves showed reasonably good correlations with the RI.